The Effects of Experience, Ownership, and Knowledge on IPO Survival: Empirical Evidence from Germany - David B. Audretsch; Erik E. Lehmann (Max Planck Institute for Research into Economic Systems, 2004)
We study the implications of ownership and its induced incentives on firm survival on the stock market for young and high-tech firms. Using a unique data set of all 341 firms listed on the Neuer Markt, the German counterpart of the NASDAQ, our results differ from studies on more traditional firms. Ownership by CEOs has no influence on firm survival when introducing measurements of human capital and intellectual property rights. This confirms assumptions that firms in the knowledge based industries differ also in their governance structure from traditional firms.
Keywords: C14; M13; L11; G32; 330; Firm Survival; Corporate Governance; New Economy; Entrepreneurship; Unternehmensgründung; Unternehmensentwicklung; Neuer Markt; Eigentümerstruktur; Corporate Governance; Humankapital; Wissen; Wertpapieremission; Schätzung; Deutschland